1984
DOI: 10.1152/ajpregu.1984.246.1.r26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and gonadectomy on food intake, body weight, and body composition in Siberian hamsters

Abstract: Two experiments examined the effects of gonadectomy, photoperiod, and melatonin treatment on food intake, body weight, and carcass composition in male and female Siberian hamsters (Phodopus sungorus sungorus). Gonadectomy caused small decreases in body weight in both sexes but did not affect food intake. In males the weight reduction was due to small (nonsignificant) decreases in all carcass components. Ovariectomy caused a significant reduction in carcass lipid but did not affect lean body mass. A short photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 0 publications
10
119
0
Order By: Relevance
“…Finally, although well after these seminal studies reporting brite/beige adipocytes in traditionally WAT depots 2002 (ref 22) , but before the most recent flurry of brite/ beige cell 'rediscovery', we found that Siberian hamsters (Phodopus sungorus) transferred from long 'summer-like' photoperiods (light:dark 16:8 h) to short 'winter-like' photoperiods (light: dark 8:16 h) in the laboratory with typical vivarium ambient temperature (~22-23°C) had increased WAT β 3 -adrenoceptor and UCP-1 gene expressions in retroperitoneal WAT (the only WAT pad tested for these responses 22 ). These data showed for the first time, to our knowledge, that a naturally occurring reversal of an obese state (~50% body fat to~20% body fat 23 ) that induces increases in the sympathetic drive to WAT 24 also triggers browning, doing so without decreases in ambient temperature. 22 Collectively, the finding of brownish (brite/beige) adipocytes in WAT depots that were thought to be the province of only white adipocytes, has a 30-year history, but despite this, only recently has this been recognized as a common phenomenon across many mammalian species including humans.…”
Section: Methodsmentioning
confidence: 61%
“…Finally, although well after these seminal studies reporting brite/beige adipocytes in traditionally WAT depots 2002 (ref 22) , but before the most recent flurry of brite/ beige cell 'rediscovery', we found that Siberian hamsters (Phodopus sungorus) transferred from long 'summer-like' photoperiods (light:dark 16:8 h) to short 'winter-like' photoperiods (light: dark 8:16 h) in the laboratory with typical vivarium ambient temperature (~22-23°C) had increased WAT β 3 -adrenoceptor and UCP-1 gene expressions in retroperitoneal WAT (the only WAT pad tested for these responses 22 ). These data showed for the first time, to our knowledge, that a naturally occurring reversal of an obese state (~50% body fat to~20% body fat 23 ) that induces increases in the sympathetic drive to WAT 24 also triggers browning, doing so without decreases in ambient temperature. 22 Collectively, the finding of brownish (brite/beige) adipocytes in WAT depots that were thought to be the province of only white adipocytes, has a 30-year history, but despite this, only recently has this been recognized as a common phenomenon across many mammalian species including humans.…”
Section: Methodsmentioning
confidence: 61%
“…Body mass was recorded every other day for this group, and food access was adjusted so that the LD-FR group mean body mass tracked the SD-AL group mean. We modulated food availability to the LD-FR group to target the pattern of body mass loss in the SD-AL group, rather than providing food quantities that were pair matched to SD-AL food intake, because body mass loss in short days is influenced by other factors in addition to food intake (Wade and Bartness, 1984).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…When Siberian hamsters are exposed to long days (LDs), they develop a severe obesity [?50% body fat (17)(18)(19)], a level as extreme as that seen in genetically inbred strains of rats and mice [e.g., ob/ob mice (20) and Zucker fa/fa rats (21)]. The LD-induced obesity of Siberian hamsters is completely reversible by exposure to short days (SDs), with the decrease in body fat being most rapid during the first 5-6 weeks of SDs (17,18,(22)(23)(24).…”
Section: Changes In the Photoperiod (Daylength) Trigger A Naturally Omentioning
confidence: 99%
“…The LD-induced obesity of Siberian hamsters is completely reversible by exposure to short days (SDs), with the decrease in body fat being most rapid during the first 5-6 weeks of SDs (17,18,(22)(23)(24). Moreover, the body fat loss during this time occurs without a concomitant decrease in food intake but eventually (.6 weeks of SD exposure) is accompanied by an ?30% decrease in food intake (17,25,26); thus, the initial body fat loss is attributable to increased energy expenditure.…”
Section: Changes In the Photoperiod (Daylength) Trigger A Naturally Omentioning
confidence: 99%
See 1 more Smart Citation